2015
DOI: 10.1620/tjem.236.281
|View full text |Cite
|
Sign up to set email alerts
|

Lower Barthel Index Is Associated with Higher Risk of Hospitalization-Requiring Pneumonia in Long-Term Care Facilities

Abstract: Pneumonia is an important infectious entity that affects residents in long-term care facilities (LTCFs), whereas hospitalization-requiring pneumonia (HRP) represents a more critical patient condition with worse outcomes. The evidence addressing the association between Barthel index and risk of HRP among LTCF residents is lacking. A multicenter, retrospective cohort study was conducted in three LTCFs enrolling adult patients who resided for 3 months or more and ever underwent Barthel index evaluation within a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…24 Studies of primarily institutionalized patients have reported that a low BI is associated not only with increased risk of nursing homeacquired pneumonia, but also with increased mortality. 25 A prospective observational study of factors other than the PSI associated with pneumonia mortality found a BI < 80 was more important than other factors, such as age or comorbidities, and as important as the PSI in predicting the prognosis of elderly patients with pneumonia. 19 This is particularly relevant in the case of institutionalized patients, in whom a low BI is a major determinant of the need for hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…24 Studies of primarily institutionalized patients have reported that a low BI is associated not only with increased risk of nursing homeacquired pneumonia, but also with increased mortality. 25 A prospective observational study of factors other than the PSI associated with pneumonia mortality found a BI < 80 was more important than other factors, such as age or comorbidities, and as important as the PSI in predicting the prognosis of elderly patients with pneumonia. 19 This is particularly relevant in the case of institutionalized patients, in whom a low BI is a major determinant of the need for hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Maryland State Med Journal 1965; 14:56-61. Used with permission [15,16]. BI consists of 10 ADL, each of which is graded as 0, 5, or 10 with a maximum total score of 100 [17].…”
Section: Measurement Instrumentsmentioning
confidence: 99%
“…In CAP, a worse ADL is directly related to increased immediate and long-term mortality [32] . It was reported that a BI level 80 was associated with 30-day mortality in pneumonia patients [33] and a low BI with increased mortality in institutionalized patients [34] . On the other hand, a high BI level has been reported was related to reduced 30-day and 18 months mortalities in elderly CAP patients [35] .…”
Section: Discussionmentioning
confidence: 99%